Synthesis of 2-Arylamino-1,3,5-triazines from 2-Aminotriazines with Aryl Halides via CuI-Catalyzed Ullmann Coupling Reaction - Li, Jin Jing; Wu, Kong; Zhou, Wei; Wang, Hong; Cui, Dong-Mei; Zhang, Chen (Synlett, 2016)
An efficient copper-catalyzed synthesis of 2-arylamino-1,3,5-triazines from 2-aminotriazines with aryl halides under mild conditions has been developed. The reaction occurred in moderate to good yields and tolerated aryl iodides containing functionalities such as nitriles, ethers, amides, and halogens. Aryl bromides were also well tolerated.
Keywords: aryl halides; 2-aminotriazines; 2-arylamino-1,3,5-triazines; copper catalyst; coupling reaction